El premio de la plata y la devaluación del vellón en Guipúzcoa en el siglo XVII - Aragón Ruano, Álvaro; Alberdi Lonbide, Xabier (Cuadernos de Historia Moderna, 2002)
The next article analises the evolution of the silver’s prize during the XVIIth Century in Guipuzcoa, where there arise two trends of behaviour, always related to the movement and abundance of the silver, which are the main factors that explain the changes of the prize. It is verified, nevertheless, that in each town the prizes are different, which shows the local economies’ autonomy in the Ancient Regime. Besides, we should add that the main repercussion of this phenomenon was reflected in the local markets and transactions, mainly affecting the communities. In any case, it is stated the need to continue investigating in the different territories which formed the Crown, and to stamp out definetely the generalization of data, such as Hamilton’s one.
Keywords: Silver; old copper coin; devaluation; Guipúzcoa; XVIIth Century